The Golden Age of the Quantity Theory. - Laidler, David E. W. (Princeton legacy library., 2014)
How did neoclassical monetary economics, as epitomized by the work of Fisher, Wicksell, and the Cambridge School, evolve from the classical orthodoxy that dominated economics in the 1870s? To answer this question, David Laidler considers the interaction of theoretical developments with contemporary policy debates about bimetallism and the evolution of the gold exchange standard. He argues that neoclassical monetary economics, in which the quantity theory of money played a central role, laid the intellectual groundwork for the replacement of the gold standard by various managed monetary syst.